2019
DOI: 10.1029/2017jc013704
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the Imprint of River Runoff Variability on Arctic Water Mass Transformation

Abstract: The Arctic Ocean receives a net freshwater input from land and from the atmosphere. This flux of freshwater, along with net surface heat loss, acts to transform the water mass properties of inflowing Atlantic and Pacific waters. In this study, model simulations are used to quantify the Arctic water mass transformation in salinity and temperature space, and its explained variance due to variability in the largest freshwater source to the Arctic: river runoff. This explained variance is quantified using a novel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…Other outstanding issues related to Beaufort Gyre freshwater content, which have required modeling approaches, relate to understanding the role of meteoric water (river runoff plus net precipitation; see Lambert et al, 2019, and, and Kelly, Proshutinsky, Popova.et al, (2018), in this special collection) in the observed freshwater content changes, mechanisms for Pacific water transport into the Beaufort Gyre and better understanding of the role of eddies in Beaufort Gyre stabilization (Manucharyan & Isachsen, 2019;, in this special collection).…”
Section: Beaufort Gyre Observing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Other outstanding issues related to Beaufort Gyre freshwater content, which have required modeling approaches, relate to understanding the role of meteoric water (river runoff plus net precipitation; see Lambert et al, 2019, and, and Kelly, Proshutinsky, Popova.et al, (2018), in this special collection) in the observed freshwater content changes, mechanisms for Pacific water transport into the Beaufort Gyre and better understanding of the role of eddies in Beaufort Gyre stabilization (Manucharyan & Isachsen, 2019;, in this special collection).…”
Section: Beaufort Gyre Observing Systemmentioning
confidence: 99%
“…The imprint of river runoff variability is examined by Lambert et al (2019) and Brown et al (2019) in this special collection. Grivault et al (2018) evaluate the water transport and volume of fresh water flowing through the straits of the Canadian Arctic Archipelago.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…Pemberton and Nilsson (2016) performed runoff sensitivity experiments in an ocean/sea-ice model that enhanced runoff and shallowed the halocline, while also modifying the Atlantic water inflow. Lambert et al (2019) used a climate response function approach to show the diffusion of heat and salt in the Arctic increased under enhanced runoff, eventually leading to enhanced advective imports of salt and heat into the Arctic.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ocean currents passing through the Bering Strait make a significant contribution to the input of OCPs to the Arctic Ocean, particularly for β‐hexachlorocyclohexane (β‐HCH) (Li et al, 2002). River runoff carries land‐based OCPs from soils, dry or wet absorption, and snow and ice meltwater into the large Arctic drainage basin, which arguably is mostly the result of prior LRAT (Cai et al, 2012; Lambert et al, 2019; Ma et al, 2018). OCPs from atmospheric, oceanic, and riverine sources thus converge in the Arctic Ocean (Bidleman et al, 2015; Cabrerizo et al, 2018; Hung et al, 2016), with Arctic regions acting as reserves and secondary sources of OCPs (Ma et al, 2016).…”
Section: Introductionmentioning
confidence: 99%